2022
DOI: 10.3390/su14073941
|View full text |Cite
|
Sign up to set email alerts
|

Millets and Cereal Meals from the Early Iron Age Underwater Settlement of “Gran Carro” (Bolsena Lake, Central Italy)

Abstract: Archeobotanical materials recovered from pottery vessels originating from the underwater archeological site of “Gran Carro”, located in Central Italy on the shore of Bolsena Lake, were analyzed to obtain new insight into the agricultural habits present in this Iron Age settlement. The archeobotanical study of cereal remains was combined with analytical data obtained from an amorphous organic residue using optical microscopy, SEM-EDS, ATR/FT-IR and Py-GC/MS. The cereal remains of emmer wheat (Triticum dicoccum)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Broomcorn millet became a common culture during the Iron Age in northern and central Italy (ca. 3100-2400 cal yr BP; [83]), while in Roman times, the consumption of millet was reserved for animal feed and it was deemed suitable only for the poor as it was considered a low-quality cereal [84]. In general, archaeobotanical evidence suggests a minor presence of millet compared to other cereal crops at Roman sites [85].…”
Section: The Combined Evidence Of Panicum Pollen and Sedimentary Mili...mentioning
confidence: 99%
“…Broomcorn millet became a common culture during the Iron Age in northern and central Italy (ca. 3100-2400 cal yr BP; [83]), while in Roman times, the consumption of millet was reserved for animal feed and it was deemed suitable only for the poor as it was considered a low-quality cereal [84]. In general, archaeobotanical evidence suggests a minor presence of millet compared to other cereal crops at Roman sites [85].…”
Section: The Combined Evidence Of Panicum Pollen and Sedimentary Mili...mentioning
confidence: 99%
“…The compositional data was acquired using the Esprit1.9 software and a standardless quantification. The SEM images were acquired in the backscattering mode [16].…”
Section: Variable Pressure Scanning Electron Microscope Coupled With ...mentioning
confidence: 99%
“…To increase the number of bioactive compounds, with high-intensity ultrasound treatment, the results showed that with an amplitude of 80% for 12.5 minutes, the number of antioxidants increased by 15% (Mustac et al, 2019). Archaeobotanical studies of the Iron Age in Central Italy using SEM-EDS, ATR/FT-IR, and Py-GC/MS show that millet (Panicum miliaceum) has become the plant of choice for food besides wheat (Fundurulic et al, 2022). Millet flour as a food raw material has been a tradition since 202 BC, the result of the characterization of leftovers from cereals, meat, and kebabs found in Changle Cemetery (202SM-220M) using Fourier Transform Infrared Spectroscopy (FTIR), starch grain, phytolith, stable isotope analysis, and proteomics show that the food is made from millet seeds and millet flour with the addition of barley flour and beef (Ren et al, 2022).…”
Section: Introductionmentioning
confidence: 99%